2020
DOI: 10.1039/d0ma00606h
|View full text |Cite
|
Sign up to set email alerts
|

Guest-conditioned multicolor writing on cellulose nanocrystal canvases

Abstract: Supramolecular smart paper has been created by embedding ionic macrocycles within cellulose nanocrystal films. The films can be written on with inks composed of colourless π-electron-rich molecules to reveal colourful, rewriteable patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Guests Gp2 and Gn2 have phenylene and naphthalene cores, respectively, and two ethylene oxide units on their side arms; both Gp2 and Gn2 can form distinctive, colorful host−guest complexes in solution and in the gel states upon binding with CBPQT 4+ . 33 Gp2 and Gn2 show almost identical hydrodynamic radii (R H = 0.44 and 0.46 nm, respectively; see Table S2). Their different π-electron character, however, differentiates the self-assembly properties of Gp2 and Gn2 with CBPQT 4+ .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Guests Gp2 and Gn2 have phenylene and naphthalene cores, respectively, and two ethylene oxide units on their side arms; both Gp2 and Gn2 can form distinctive, colorful host−guest complexes in solution and in the gel states upon binding with CBPQT 4+ . 33 Gp2 and Gn2 show almost identical hydrodynamic radii (R H = 0.44 and 0.46 nm, respectively; see Table S2). Their different π-electron character, however, differentiates the self-assembly properties of Gp2 and Gn2 with CBPQT 4+ .…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shifts for the aromatic signals matched well with those reported for compounds Gn2 (Figure S5) and Gp2. 33 This suggested that the aromatic cores retained their electron-rich character, which is important for their self-assembly with CBPQT 4+ .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations